PENGARUH REKRUTMENT DAN SELEKSI KARYAWAN EJ33 VAPE CABANG UTAMA SAMARINDA TERHADAP KINERJA INDIVIDU PASCA PANDEMI - M.Zamroji Almursyid (Jurnal Ilmu Pendidikan dan Sosial, 2022)
The effect of employee recruitment and selection on individual performance of EJ33 Vape employees, Samarinda main branch, on individual performance after pandemic. In selling the EJ33 Vape Samarind, they do it in various ways, such as buying and selling in stores, through Tokopedia, Instagram, Facebook and in the form of offers to smaller shops. EJ33 Vape Samarinda was founded in 2015 and currently has several branches. the main store location is on Jl. M. Yamin Samarinda city. With its function as a distributor of several products and a wholesaler for smaller shops, it requires more employees than usual. Researchers took 20 respondents who were then given a questionnaire to fill out. From the results of the analysis and discussion, it can be concluded that the first hypothesis of recruitment has a significant effect on employee performance is rejected on the basis of t table X1 = 0.635 < 2.093 meaning X1 has no effect on performance, hypothesis 2 Selection has a significant effect on employee performance is rejected on the basis of while t count X2 = 1.355 < 2.093 so that it can be said that the X2 variable does not have a positive effect on performance, Hypothesis 3 Recruitment and selection simultaneously affect employee performance is rejected on the basis of the significance value of the table showing a value of 0.179, which means it is greater than 0.05, thus the x variable together or simultaneously has no effect on performance.